Gamma-ray and neutrino diffuse emissions of the Galaxy above the TeV. Issue 5 (May 2016) - Gaggero, D; Grasso, D; Marinelli, A; Urbano, A; Valli, M
Abstract: Conventional cosmic ray propagation models face problems reproducing the diffuse 7-ray spectrum measured by Fermi-LAT over the entire sky. Those models also fail to smoothly connect Fermi-LAT results with data above the TeV as those taken by Milagro in the inner Galactic plane. In this contribution we show that a representative model adopting a spatial dependent rigidity scaling of the diffusion coefficient can reproduce all those experimental results without spoiling the consistency with local cosmic-ray measurements. We use the same model to compute the diffuse neutrino emission of the Galaxy and compare it with IceCube and ANTARES results.